AD, Volume 37, n° 4, 2012 - Full Issue (Africa Development, 2021)
Contents Introduction Lansana Keita ............................1 On Deligitimising Capitalism: The Scourge of Africa and the South Samir Amin ............................. 15 Revealed Preference Theory, Rationality and Neoclassical Economics: Science or Ideology Lansana Keïta.......................... 73 An Alternative African Developmentalism: A Critique of Zero-sum Games and Palliative Economics Yves Ekoué Amaizo.................117 Africa’s Growth and Development Strategies: A Critical Review Musibau Adetunji Babatunde....... 141 Africa’s Developmental Impasse: Some Perspectives and Recommendations Demba Moussa Dembele..............179 The Economic Situation in Contemporary Africa: Comment on Questions Posed by Lansana Keita Patrick Bond & Demba Moussa Dembele........197 African Elites and their Post-colonial Legacy: Cultural, Political and Economic Discontent — by Way of Literature Samba Diop..........................221 Book Review Ha-Joon Chang, Bad Samaritans: The Myth of Free Trade and Secret History of Capitalism, New York: Bloomsbury Press, 2008 Lansana Keita.....................237